HARMONIC RESONANCE: AN IN-DEPTH ANALYSIS OF PHONOLOGY IN SURAH AL-LAIL, UNVEILING POETIC SOUND HARMONY AND ITS IMPACT - Fitri, Syifa Auliaul; Uyuni, Yuyun Rohmatul (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
The Qur'an is the holy book of the Islamic Ummah which contains various features apart from the contents in it, the Al-Qur'an is also composed with beautiful and harmonious strands of verse, the purpose of this discussion is to dig deeper into the The specialty of the Qur'an in terms of its sound harmony, this discussion uses the literature study method with qualitative research studies and This data analysis technique is descriptive research which describes various data or problems and is then analyzed using a phonological approach on each word element in the verse in the form of vowels, consonants and the structure of these sounds. Al-lail's 21 verses have a final sound harmony which in badi science is called Assaj'u .assaj'u in Al-lail's letter belongs to the As-saj'u Muthorrof type where each end of the verse of this letter has a different wazan but the last letter is the same. In addition, each end of the verse of surah al-Lail consists of two letter sounds, namely vowels and consonants which give rise to beautiful and harmonious rhyme patterns. As for the vowels contained in each poem at the end of the verse of Surah Al-lail, there are 40 vowels /a/ and 8 vowels /u/. While consonants consist of 4 letters /y/, 2 letters /g/, 3 letters /sy/, 12 letters /t/, 12 letters /j/ 7 letters / n/ 4 letters /tsa/ 1 letter, letter /q/ 3 letters /h/ 3 letters /s/ three letters , letter /n/ 3 letters, /y/ 3 letters , letter /r/ 4 letters , letter /d / 3 letters, /dz/ 1 letter, /w/ 1 letter, /z/ 2 letters, 1 letter dho with a total of sixty-nine consonant letters.